Knowledge on cervical cancer screening and vaccination among females at Oyibi Community - Evans Appiah Osei; Stella Appiah; Judith Elinam Gaogli; Ezekiel Oti-Boadi (BMC, 2021)
Abstract Background Awareness about cervical cancer screening and vaccination in the developed countries are high as compared to the developing countries. Sixty to eighty percent (60-80%) of the women who develop cervical cancer in sub-Saharan Africa live in the rural areas with inadequate awareness of cervical cancer screening. However, cervical cancer knowledge remained a significant direct predictor of screening behaviors. The study therefore aim to explore the Knowledge on Cervical Cancer Screening and Vaccination among females at Oyibi Community. Methods A qualitative exploratory design was employed to purposively recruit 35 participants who were made up of 7 members in a group forming 5 Focus Group discussions in all. Data was retrieved using a semi-structured interview guide. Results The study revealed two main themes with 7 subthemes. The two main themes were cervical cancer screening and vaccination knowledge and cervical cancer vaccination effectiveness and cost. The subthemes were; knowledge on cervical cancer screening types, knowledge about cervical cancer screening and vaccination centers, knowledge about how cancer screening is performed, knowledge about cervical cancer vaccination, cervical cancer screening and vaccination sources of information, knowledge about the effectiveness of cervical cancer vaccination and awareness about cervical cancer screening cost and vaccination cost. Conclusion Ghanaian women are increasingly becoming aware of cervical cancer, nevertheless low knowledge on screening and vaccination of cervical cancer, and effectiveness was detected with high awareness about the screening and vaccination centers. There is therefore the need for heightened sensitization regarding cervical cancer screening and vaccination in rural communities to help reduce misconceptions and increase patronage rate.